Usamos todos,algunos y ninguno al clasificar objetos - Cardoza Oliva, Paula del Rosario (2018)
This learning session in the area of mathematics has allowed an improvement in first grade students to compare their strategies when solving problems in any situation of their daily lives. When we refer to classify objects or organize them according to a certain characteristic it means that they look for an immediate solution and find a hierarchical classification according to its aspects and according to the degree importance that each thing has. The objects with which the student works can be subjected to the action that the student can have: material that can be seen, touched, have shape, size, colors with which he will work. But each object can be linked to others in an immaterial way that only exists in the idea of each one Firs grade students solve problems and work in an organized manner forming groups served by the teacher